Administrative Law: Datuk James Wong v. Officer-in-Charge, Kamunting Detention Centre and Federal Secretary, Sarawak - Yusoff, Mohd Ariff (Journal of Malaysian and Comparative Law, 2018)
Administrative Law – Datuk James Wong v. Officer-in-Charge, Kamunting Detention Centre and Federal Secretary, Sarawak